The Impact of AFTA on Japan-ASEAN Trade Flows - Chen, Chen Yong; Hui, Boon Tan (Penerbit Universiti Kebangsaan Malaysia, 2007)
Japan and ASEAN have a friendly and cooperative relationship since the 1970s. Japan is one of the most important economic partners for ASEAN, and vice versa. Japan and ASEAN member countries pursue bilateral and regional approaches to free trade agreements in order to further enhance their competitiveness. The ASEAN Free Trade Area (AFTA) was established in 1992. Along with the regional approaches, the bilareral approach to economic partnership between Japan and ASEAN is increasingly important in order to move toward greater economic integration in Asia. ASEAN has sustained trade deficifs with Japan for a long time and its exports have been heavily reliant on Japanese market. From this point of view, Japan has been a relatively important market for ASEAN but not vice versa; and Japan has been a comparatively important supplier to ASEAN but not vice versa Structural changes in the trading patterns between Japan and ASEAN in such a way that reflects a complementary relationship between the two regions remains in doubt. Although intra-ASW trade has registered growth afer the implementation of AFTA, but ASEAN still encounters a large deficit with Japan. Therefore, changes in trade volume between Japan and ASEAN through the trade creation eflect or trade diversion efect resultedfiom the establishment of AFTA are questionable. This study attempts to empirically examine the impact of AFTA on trade linkages between Japan and ASEAN-5co untries, namely, Malaysia, Singapore, Thailand, Indonesia and the Philippines using annual data from 1970 to 2003. An estimation method known as Vector Error Correction Model was used. The result shows that although AFTA has led to trade creation between Japan and ASEAN-5 countries but trade elationship between Japan and ASWre mains asymmetry.